Performa Pertumbuhan Sargassum cristafolium Di Teluk Gerupuk Lombok Tengah - Cokrowati, Nunik (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2024)
Sargassum cristafolium seaweed is a seaweed that has a dominant polysaccharide content including alginate, laminarin, and fucoidan which is usually used in the food, textile, pharmaceutical, agricultural, and cosmetic industries. So with the many benefits that S. cristafolium has, it causes the export volume of seaweed to increase so that production indirectly also increases. However, S. cristafolium has not been cultivated on a mass basis in NTB, especially on the island of Lombok. So with the potential of S. cristafolium seaweed supported by the Gerupuk Bay aquatic environment, it is suitable for cultivation. But at the level of cultivators, what is still a problem is the use of early seaweed seeds. So the purpose of this study was to analyze the differences in the growth of S. cristafolium cultivated with different seed weights. The method used is an experimental method using a Completely Randomized Design (CRD). The treatments in this study consisted of 5 treatments and 4 replications, namely P1 (seedling weight 100 g), P2 (seedling weight 75 g), P3 (seedling weight 50 g), P4 (seedling weight 25 g), P5 (seedling weight 125 g). Data were analyzed using Analysis of variance (ANOVA) and then continued with Duncan's test with a 95% confidence level. The best absolute growth research results were in the P1 treatment (seed weight 100 g) which was 91.25 g. While the best specific growth rate was in treatment P4 (seedling weight 25 g) with a value of 7.84%. This study concluded that different seed weights affected the growth of S. cristafolium seaweed.